Still on the trail. (Economist, 2017)
The article discusses the bank heist which took place in Bangladesh. The incident so happened that a group of hackers had sent a set of instructions to the central bank of the country through Society for Worldwide Interbank Financial Telecommunication. About $ 101 million was stolen and most of it is yet to be retained. However, recent investigations of the authorities working on the case have suggested that it was done foreign hackers who had received some form of help from inside the country.